The Great Cycle of the star Sothis: catasterism in the bronze emissions of Antoninus Pius with zodiacal theme from the mint of Alexandria = Wielki Cykl gwiazdy Sotis; katasteryzm na aleksandryjskich brązowych emisjach Antonina Piusa z motywem zodiakalnym - Ceci, Francesca (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 139 AD, under the reign of Antoninus Pius, an astronomical event of great importance for Egypt took place: the Great Cycle of the star Sothis, identified with Sirius of the constellation of the Dog, in which the star touched the same point on the horizon reached by the Sun once every 1461 years: this moment began a new era, the Sothiac cycle.
Keywords: Zodiac; Antoninus Pius (cesarz rzymski; 19-161); mint of Alexandria; Sothiac cycle; zodiak; mennica aleksandryjska; cykl sotisowy